Blood lactate testing in training. Is it worthwhile? - Bowman, S. (2001)
Thus many debateable issues contribute to the debate concerning the se of BL as a valid and reproducible physiological test to predict endurance performance. Timing (Myburgh et al,2000) design (Foxdal et al 1994) and intensity (Palmer et al,1999) coupled with sampling, analysis and calculation issues (Foxdal et al 1994) compound the spurious nature for inference. Albrecht (1998) used rating of perceived exertion and performance results to conclude that BL was a more favourable LT test than Heart Rate, as HR fails to provide an accurate physiological profile in response to exercise intensity testing.